The Influence of Leg Muscle Explosive Power and Waist Fitness towards Screen Kick Speed for Pencak Silat Students at PSHT UNDHARI - Chintiya Sari Monica; Dian Estu Prasetyo; Maldin Ahmad Burhan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
The background of this research is the low kick speed of the PSHT Pencak Silat athletes from the UNDHARI Commissariat. Efforts to overcome these problems require training Leg Muscle Explosive Power and Waist Flexibility. This study aims to find out whether leg muscle explosive power training and waist flexibility have an effect on the sickle kick speed of PSHT pencak silat athletes. This research is a type of quantitative research using an experimental method approach. While the form of research design used is